2021
DOI: 10.1038/s41598-021-88362-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in-hospital deprescribing on potential prescribing omission in hospitalized elderly patients with polypharmacy

Abstract: No studies to investigate the effect of a deprescribing intervention on the occurrence of potential prescribing omissions (PPOs) among elderly patients with polypharmacy have been conducted. Therefore, the effect of deprescribing on PPOs among elderly patients with polypharmacy was investigated. All 121 consecutive elderly patients who received in-hospital deprescribing interventions were evaluated. The primary outcome was any occurrence of PPOs based on the 2015 STOPP/START criteria. The proportion of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 57 In this context, efforts to minimise polypharmacy and deprescribe unnecessary or inappropriate medications were described around the world. 58–69 Recently, findings from a Swiss cluster randomised clinical study among 46 primary care physicians suggested that a patient-centred deprescribing intervention may reduce polypharmacy among old multimorbid patients. 67 In Portugal, an ongoing nationwide three-phase study on deprescribing is investigating barriers and facilitators of deprescribing perceived by older adults and their acceptance to have regular medications deprescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 In this context, efforts to minimise polypharmacy and deprescribe unnecessary or inappropriate medications were described around the world. 58–69 Recently, findings from a Swiss cluster randomised clinical study among 46 primary care physicians suggested that a patient-centred deprescribing intervention may reduce polypharmacy among old multimorbid patients. 67 In Portugal, an ongoing nationwide three-phase study on deprescribing is investigating barriers and facilitators of deprescribing perceived by older adults and their acceptance to have regular medications deprescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, about 50% of older adults take at least one unnecessary medication56 and less than 50% have a clear understanding of pharmacotherapy purpose 57. In this context, efforts to minimise polypharmacy and deprescribe unnecessary or inappropriate medications were described around the world 58–69. Recently, findings from a Swiss cluster randomised clinical study among 46 primary care physicians suggested that a patient-centred deprescribing intervention may reduce polypharmacy among old multimorbid patients 67.…”
Section: Discussionmentioning
confidence: 99%
“…Potential limitations also need to be acknowledged. In particular, medication changes during hospitalization, including targeted deprescribing strategies (Tay et al, 2014;Russell et al, 2019;Kaminaga et al, 2021;Roberts et al, 2021;Russell et al, 2021;Scott et al, 2021), inevitably lead to deviations from the medication list on admission. This, however, could be rectified by additional linkage to discharge and/or readmission data.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization of drug treatment is challenging, as both overtreatment and undertreatment issues may exist simultaneously in older people (Kaminaga et al, 2021). Therefore, some medication screening strategies have been created to help physicians optimize prescribing for older adults (Jansen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%